1987
DOI: 10.1046/j.1468-2982.1987.0702131.x
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroergotamine Nasal Spray During Migraine Attacks: A Double-Blind Crossover Study with Placebo

Abstract: Ergot derivatives have been used in the treatment of migraine for more than 50 years. We have compared the efficacy of dihydroergotamine (DHE) nasal spray with that of placebo in patients with classic or common migraine attacks. The study was performed in accordance with a double-blind, crossover design. In this study a great placebo effect was observed with a dose of 1.36 mg/attack, and the overall efficacy was rated by the patients to be 41% and 52% for placebo and DHE, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…The difference between the lower dose of DHE (0.5 to 1 mg) and placebo was statistically significant, but the differences between the higher dose of DHE and placebo and between the 2 DHE doses, were not. The remaining 2 trials found similar differences in the overall proportion of patients using DHE and placebo who reported adverse events (20% versus 7% and 29% versus 11%, respectively), 93,94 though the difference was statistically significant only for Ziegler et al 94 …”
Section: Intranasal Dihydroergotaminementioning
confidence: 95%
See 4 more Smart Citations
“…The difference between the lower dose of DHE (0.5 to 1 mg) and placebo was statistically significant, but the differences between the higher dose of DHE and placebo and between the 2 DHE doses, were not. The remaining 2 trials found similar differences in the overall proportion of patients using DHE and placebo who reported adverse events (20% versus 7% and 29% versus 11%, respectively), 93,94 though the difference was statistically significant only for Ziegler et al 94 …”
Section: Intranasal Dihydroergotaminementioning
confidence: 95%
“…Four of the above comparisons with placebo provided effect size estimates suitable for meta‐analysis 90,92‐94 . We chose the effect size for the higher dose of DHE (1 to 4 mg) in the Paiva et al study, 90 because that dose was closer to the doses used in the other trials.…”
Section: Intranasal Dihydroergotaminementioning
confidence: 99%
See 3 more Smart Citations